2007
DOI: 10.1177/0018726707081661
|View full text |Cite
|
Sign up to set email alerts
|

Making career choice: A study of Chinese managers

Abstract: Compared with the extensive research on managerial careers in the West, little has emerged from China and South-East Asia. This exploratory study used Schein's concept of Career Anchors to investigate how 117 Taiwanese managers made their initial career choice and the values which shaped their subsequent careers. The findings indicate how cultural specificity and political dynamics impacted on the managers' career experience. The Taiwanese subjects valued independence, a balanced lifestyle and entrepreneurial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
2
29
1
Order By: Relevance
“…As the parents of MIS professionals in the 40-49 age group get older, the responsibility for their care will rest with those professionals. At the same time, they need more time to take care of their own children and family, results that are consistent with the findings of Hofstede (1983), andWong (2007). In addition, the 40-49 age group is less likely to seek new employment within a specific geographic area.…”
Section: Servicesupporting
confidence: 80%
See 1 more Smart Citation
“…As the parents of MIS professionals in the 40-49 age group get older, the responsibility for their care will rest with those professionals. At the same time, they need more time to take care of their own children and family, results that are consistent with the findings of Hofstede (1983), andWong (2007). In addition, the 40-49 age group is less likely to seek new employment within a specific geographic area.…”
Section: Servicesupporting
confidence: 80%
“…Joseph et al (2007) developed a contextual turnover model for information technology professionals, believing that national culture is another important factor. In a study of Chinese managers in Taiwan, Wong (2007) drew a similar conclusion. In addition, Joseph et al (2007) incorporated the job embeddedness theory (Mitchell, Holtom, Lee, & Erez, 2001) into the turnover process at the individual level.…”
Section: Career Anchors and Job Turnover In The Literaturementioning
confidence: 77%
“…The factor structure was somewhat problematic even in the sample of established professionals with which we conducted our exploratory factor analysis. We are not the first to point this out (Danziger and Valency 2006;Danziger, Rachman-Moore, and Valency 2008;Feldman and Bolino 1996) and in this regard it is surprising that many studies simply assume the scales' validity and reliability (e.g., Igbaria, Greenhaus, and Parasuraman 1991;Wong 2007;Yarnall 1998). Noting Feldman and Bolino's (1996) reservations, we tested the scales and our tests rendered inconsistent results (e.g., Danziger, Rachman-Moore, and Valency 2008).…”
Section: Downloaded By [New York University] At 00:28 02 August 2015mentioning
confidence: 88%
“…The Lagrange multiplier (LM) test suggested adding parameters estimating covariance among factors. Although Schein's original work proposed independence between career anchors, recent research (Wong 2007) has suggested career anchors can be correlated. Model 3 thus freed the restrictions on factor covariance from Model 2 and allowed for correlations among the factors to be freely estimated.…”
Section: Confirmatory Factor Analyses In the Student Samplementioning
confidence: 99%
“…It is generally accepted that parents serve as mentors and role models for their children's choice of a career. Nonetheless, depending on their attitude towards work and disability, sometimes parental expectations limit career choice of differently abled children (Wong, 2007;Zellweger, Sieger & Halter, 2010).…”
Section: Features Of the Framework On Career Construction For Hephaprmentioning
confidence: 99%